Surgical Management of a High‐Grade Gastrointestinal Stromal Tumor in a Morbidly Obese Patient: A Case Study - Felipe Quistian; Kristen M. Quinn; Michael A. Deal; Rana Pullatt (Medicine Advances)
ABSTRACT Gastrointestinal stromal tumors (GISTs) are the most commonly occurring mesenchymal tumors within the gastrointestinal (GI) tract yet, those located at the gastroesophageal junction (GEJ) are rare. We present a 31‐year‐old woman with morbid obesity and large (4.9 cm) polypoid mass adjacent to the GEJ. She was offered a laparoscopic transgastric GIST resection and adjuvant imatinib. Intraoperatively, a gastrotomy was created through which the polypoid tumor was successfully delivered for resection. The increasing prevalence of obesity can pose unique challenges to peri‐operative management. Thoughtful innovations in surgical approach can save obese patients from increased morbidity or surgical delay.